Kinetics of Micellar Effect of Non-Ionic Surfactant on Oxidative Degradation of Ciprofloxacin - Singh, Ajaya Kumar; Shrivastava, Alpa; Shrivastava, Dilip R.; Patel, Rajmani; Sachdev, Neerja (Asian Journal of Chemistry, 2019)
Oxidative degradation kinetics of leading fluoroquinolone family drug ciprofloxacin (CIP) by chloramine-T (CAT) in TX-100 micelle media was studied spectrophotometrically at 275 nm and 298 K. In pseudo-first-order conditions the rate constant (kobs) decreased regularly with increasing [TX-100]. To understand the self-organizing activities of TX-100, CMC values in varying reaction conditions had been evaluated. The role of non-ionic surfactant in the oxidative degradation process of ciprofloxacin by chlorinating agent chloramine-T is explained in terms of mathematical model explained by Menger-Portnoy. The reaction showed first to zero order dependence on [CAT] and fractional order on [CIP]. Increasing [H+] decreased the rate of reaction. The effect of ionic strength and solvent polarity of the medium in reaction conditions were studied. The effects of added salts [HSO4Na], [KCl], [KNO3] and [K2SO4] had also been studied. The stoichiometry of the reaction determined was 1:2 and the oxidation products were identified by LC-EI-MS. The analysis of degradation product of ciprofloxacin evidently reveals that the piperazine moiety is active site for oxidation in the reaction. Activation parameters were studied to propose appropriate mechanism for the reaction.